Cognitive-Behavioral therapy to change cognitive distortions among adolescents with Bipolar II Disorder - Darusman, Mhd. Ricky; Hidayati, Diana Savitri (Universitas Muhammadiyah Malang, 2024)
Bipolar II disorder is a mood disorder characterized by extreme changes between the hypomanic period and depressive period. Hypomanic is a period that takes at least four days where a person experiences a high mood, excited, energetic, and impulsive conditions. However, hypomania does not reach the level of severe manic as in bipolar I. Meanwhile, the depressive period is characterized by feelings of sadness, hopelessness, loss of interest in activities involvement, and other depressive symptoms. Individuals with bipolar II experience significant mood swings between hypomania and depression. The purpose of this study is to see the effectiveness of cognitive behavioral therapy by reducing the symptoms of bipolar II disorder among adolescents. The subject of the study is a 16-year-old female. The assessment method used clinical interviews, observations, and psychological test tools. The intervention used cognitive-behavioral therapy. The results of the study have showed that there is a decrease in cognitive distortion and awareness in recognizing the mood changes to anticipate more extreme mood swings. Gangguan bipolar II merupakan gangguan mood yang ditandai dengan perubahan ekstrim antara periode hipomanik dan periode depresi. Hipomanik adalah suatu periode yang memakan waktu setidaknya empat hari di mana seseorang mengalami kondisi suasana hati yang tinggi, bersemangat, energik, dan impulsif. Namun hipomania tidak mencapai tingkat manik yang parah seperti pada bipolar I. Sedangkan masa depresi ditandai dengan perasaan sedih, putus asa, kehilangan minat untuk terlibat dalam aktivitas, dan gejala depresi lainnya. Individu dengan bipolar II mengalami perubahan suasana hati yang signifikan antara hipomania dan depresi. Tujuan penelitian ini adalah untuk melihat efektivitas terapi perilaku kognitif dengan mengurangi gejala gangguan bipolar II pada remaja. Subjek penelitian adalah seorang perempuan berusia 16 tahun. Metode penilaian menggunakan wawancara klinis, observasi, dan alat tes psikologi. Intervensinya menggunakan terapi kognitif-perilaku. Hasil penelitian menunjukkan adanya penurunan distorsi kognitif dan kesadaran dalam mengenali perubahan suasana hati untuk mengantisipasi perubahan suasana hati yang lebih ekstrim.